2021
DOI: 10.1016/j.transci.2021.103068
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic anaemia and transfusion thresholds in ICU patients with COVID-19 disease at a tertiary care hospital

Abstract: Background: Patients with severe COVID-19 disease frequently develop anaemia as the result of multiple mechanisms and often receive transfusions. The aims of this study were to assess the impact of repeated blood samplings on patients' anaemic state using standard-volume tubes, in comparison with the hypothetical use of low-volume tubes and to evaluate the transfusion policy adopted. Study design and methods: Transfusion data of mechanically ventilated non-bleeding patients with COVID-19 disease hospitalized i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…However, hospitalization goes along with repeated blood sampling or occult gastro-intestinal bleeding, which may aggravate anemia especially when erythropoiesis is impaired. In a small cohort study involving 24 ICU patients with COVID-19 it was demonstrated that repeated routine blood sampling accounts for about one third of the total patients’ red blood cell mass decrease during ICU admission [ 35 ]. Moreover, in-hospital treatment can contain comprehensive infusion therapy, which has a diluting effect on hemoglobin levels, especially in the ICU, where eventually compromised renal function may further affect erythropoiesis via reduced erythropoietin formation and increased circulating hepcidin levels [ 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, hospitalization goes along with repeated blood sampling or occult gastro-intestinal bleeding, which may aggravate anemia especially when erythropoiesis is impaired. In a small cohort study involving 24 ICU patients with COVID-19 it was demonstrated that repeated routine blood sampling accounts for about one third of the total patients’ red blood cell mass decrease during ICU admission [ 35 ]. Moreover, in-hospital treatment can contain comprehensive infusion therapy, which has a diluting effect on hemoglobin levels, especially in the ICU, where eventually compromised renal function may further affect erythropoiesis via reduced erythropoietin formation and increased circulating hepcidin levels [ 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, iatrogenic blood draws lead to loss of blood. In a study, COVID-19 patients in ICU showed a loss of about one third of the total patients’ red blood cell mass because of repeated blood sampling during the ICU stay [ 117 ]. Moreover, these patients may be suffering from pre-existing iron deficiency.…”
Section: Interplay Of Iron Parameters In Covid-19mentioning
confidence: 99%
“…The volume of blood typically needed for BGA is approximately 2 mL, for serum chemistries it is 7.5 mL, for citrate tubes it is 4.3 mL, for EDTA it is 2.7 mL, and it is up to 6 × 10-20 mL for blood cultures. A systematic review by Siegal et al pointed out that only 10% of collected 3: General ICU [1,9,10,46,49,50,60]; Medical ICU [27,29,47,48,51,54]; Medical/surgical ICU [11,56,57,62]; Surgical ICU [33,64]; other ICU [32,52,53,55,59,61,63,65].…”
Section: Discussionmentioning
confidence: 99%
“…The authors also revealed an independent correlation between the increased use of phlebotomy and the risk to develop hospital acquired anemia [29]. 3: General ICU [1,9,10,46,49,50,60]; Medical ICU [27,29,47,48,51,54]; Medical/surgical ICU [11,56,57,62]; Surgical ICU [33,64]; other ICU [32,52,53,55,59,61,63,65].…”
Section: Observational Trialsmentioning
confidence: 95%
See 1 more Smart Citation